2005
DOI: 10.1186/1478-4505-3-3
|View full text |Cite
|
Sign up to set email alerts
|

The role of NGOs in global health research for development

Abstract: BackgroundGlobal health research is essential for development. A major issue is the inequitable distribution of research efforts and funds directed towards populations suffering the world's greatest health problems. This imbalance is fostering major attempts at redirecting research to the health problems of low and middle income countries. Following the creation of the Coalition for Global Health Research – Canada (CGHRC) in 2001, the Canadian Society for International Health (CSIH) decided to review the role … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
107
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(110 citation statements)
references
References 17 publications
2
107
0
1
Order By: Relevance
“…Research is one of the main foundations of sustainable development, and the long-term development of research policies without a comprehensive research system is simply not possible [1][2][3]. Research is so important that indices such as the national investment in research, the number of researchers referred to the total population and the number of published papers are considered criteria in judging a country's progress [3].…”
Section: Introductionmentioning
confidence: 99%
“…Research is one of the main foundations of sustainable development, and the long-term development of research policies without a comprehensive research system is simply not possible [1][2][3]. Research is so important that indices such as the national investment in research, the number of researchers referred to the total population and the number of published papers are considered criteria in judging a country's progress [3].…”
Section: Introductionmentioning
confidence: 99%
“…Delisle et al (2005) identified a range of benefits of NGO participation in research. NGOs are especially well placed to: (1) suggest orientations to better align research efforts with local needs and political realities; (2) contribute to transfer of research findings towards policymakers; (3) identify and integrate equity considerations in research; and (4) facilitate community engagement and participation in the development, implementation, and uptake of research.…”
Section: Introductionmentioning
confidence: 99%
“…Minimos organizacijos vis dažniau pasitelkiamos įgyvendinant tarptautinio ir nacionalinio lygmens įvairių sveikatos priežiūros ir ugdymo sričių projektus bei programas [15,18,39,55], atliekant sveikatos srities mokslinius tyrimus bei viešinant jų rezultatus [7,13,23], propaguojant fizinę [41], psichinę sveikatą [17,52], sveiką gyvenseną [1], vykdant lėtinių neinfekcinių ligų prevenciją [36,41], tenkinant specifinių grupių (pvz., moterų, vyresnio amžiaus asmenų, profesinių grupių, vietos bendruomenių), pacientų ir jų šeimų sveikatos ir socialinius poreikius [41].…”
Section: įVadasunclassified